Risk Factors and Symptoms of Meibomian Gland Loss in a Healthy Population - Anna Machalińska; Aleksandra Zakrzewska; Krzysztof Safranow; Barbara Wiszniewska; Bogusław Machaliński (Journal of Ophthalmology)
Purpose. The aim of this study was to investigate the relationships between MGL and ocular symptoms, several systemic conditions, and key markers of ocular surface health. Methods. We included into the study 91 healthy volunteers between the ages of 20 and 77 years. We analyzed meibomian gland morphology, function, and lid margin alterations. We correlated our findings with self-reported ocular symptoms, systemic medical history, lifestyle factors, and tear film abnormalities. Results. We observed that a high ocular surface disease index, a history of either chalazion or hordeolum, experience of puffy eyelids upon waking, and foreign body sensation all appeared to be predictors of an abnormal meiboscore after adjusting for age and sex (p=0.0007; p=0.001; p=0.02; p=0.001, resp.). Multivariate logistic regression model including age and sex showed that there were three independent predictors of abnormal meiboscore: older age (OR = 1.03, 95% CI = 1.01–1.04 per year, p=0.006), postmenopausal hormone therapy (OR = 4.98, 95% CI = 1.52–16.30, p=0.007), and the use of antiallergy drugs (OR = 5.85, 95% CI = 2.18–15.72, p=0.0004). Conclusion. Our findings extend current knowledge on the pathophysiology of MGL.